Georgia Architectural and Historic Properties Survey of Rural [001] Middle east section of county, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [001] Middle east section of county, Valdosta, Ga. December 1980. 2 story rectangular clapboard house with tin gabled roof. Square posts support shed porch. Double hung sash windows with 1/1 lights and shutters. Gabled dormer. Exterior chimney. Set on brick. Sidelights around door. Sits back from road in pecan grove. Fair condition. Date of Construction: c. 1900. Possibly was once a dogtrot. Typical common house rural typical for this area.
2 story rectangular clapboard house with tin gabled roof. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 53.0 MB (55,648,294 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)